The Hershey's Kisses subtraction book - Pallotta, Jerry; Bolster, Rob (New York : Scholastic, 2002)
Uses Hershey's Kisses to teach subtraction.
"Cartwheel books."
G2
Keywords: Subtraction -- Juvenile literature; Subtraction